Long-term outcome of molecular subgroups of GIST patients treated with standard-dose imatinib in the BFR14 trial of the French Sarcoma Group. (January 2016) - Patrikidou, Anna; Domont, Julien; Chabaud, Sylvie; Ray-Coquard, Isabelle; Coindre, Jean-Michel; Bui-Nguyen, Binh; Adenis, Antoine; Rios, Maria; Bertucci, François; Duffaud, Florence; Chevreau, Christine; Cupissol, Didier; et al.
Abstract: Background: The added value of tumoural genomic profiles to conventional clinico-biological factors to predict progression-free survival (PFS) and overall survival (OS) was prospectively investigated in patients with advanced gastrointestinal stromal tumours (GIST) treated in the BFR14 study. Methods: Of the 434 included patients, mutational analysis was performed in 322 patients. Survival analysis was performed in patients with validated mutational status. Results: Mutational status was validated in 228 patients. We identified 196 patients with tumours harbouring 200 KIT alterations (exon 11: 173 patients, exon 9: 22 patients, exon 17: 3 patients, exon 13: 2 patients; 4 patients had double KIT mutations), 6 patients with PDGFRA mutations and 26 patients with wild-type (WT) GIST genotype. On a median follow-up of 73 months, median PFS/OS were 12.3/54.9 months for WT GIST, 12.6/55 months for KIT exon 9, and 39.4 months/not reached (69.1% at 5 years) for KIT exon 11. Tumour size, female gender, KIT exon 11 mutations and CD34 positivity were independent prognostic factors for a higher PFS. A higher OS was predicted by performance status (PS) <2, low neutrophil and normal lymphocyte counts, KIT exon 11 mutations, non-advanced tumour and female gender. KIT exon 11 mutations at codons 557–558 showed better tumour response (p=0.028) but shorter PFS (p=0.0176). Conclusions: In GIST patients, presence of a KIT exon 11 mutation is an independent prognostic factor for PFS and OS, along with gender, PS, tumour size, lymphocyte and neutrophil counts. Subsets of exon 11 mutations are associated with significantly different response patterns and PFS. Highlights: KIT exon 11 mutation is an independent prognostic factor for PFS and OS in GIST patients. Clinico-biological factors (gender, PS, tumour size, lymphocyte & neutrophil count) are also significant. Subsets of exon 11 mutations have significantly different response patterns and PFS in GIST patients.